ICP11 as Biomarker for WSSV Disease in Litopenaeus vannamei - Yuni Kilawati; Yunita Maimunah; Arning W. Ekawati (Research Journal of Life Science, 2015)
Environmental pollution could directly reduce water quality for shrimp cultivation. This study aims to determine how the environmental quality, shrimp population and genetic characteristics of shrimp that live in polluted waters in shrimp ponds in East Java associated with WSSV disease that often attacks on cultivated shrimp. The method used was a descriptive exploratory. Data collection was collected by observation and interview with farmers on disease history. Water was sampled for water quality study and characterize its suitability for shrimp cultivations. Shrimps were also sampled for morphological and genetical study for its susceptibility of WSSV. All samples were taken every week during shrimp cultivation in Malang ans Gresik. Morphological study using scoring method to determine the disease stages on shrimp, while for genetical study using specific primer for ICP11 for WSSV detection, since ICP 11 is expressed when WSSV infection is occur. Samples were taken from 2 shrimp ponds in South Malang and Gresik.The overall water quality is good, except for NO2 and TOM in both seawater shrimp ponds which higher than the freshwater/estuary shrimp ponds. Light infections of WSSV were detected in all seawater ponds both in morphology and genetics. However, in the freshwater/estuary pond only shrimps from freshwater/estuary Gresik which showing light WSSV infection genetically, but not in the morphological signs. Early disease detection is important to control the disease spread.